Professionals$1 (BPerceived Influence on Outcomes of Multisystem-Involved Youths - Annee Grayson; Kassandra Spurlock
Youth involved in multiple systems, such as special education, juvenile justice, and foster care, often face complex challenges. Professionals inherently contribute to youth outcomes by supporting multisystem-involved youth. Through interviews, we explored the perspectives of a special education teacher, a school resource officer, a school administrator, and a youth parole supervisor to understand their perceived influence on youth. We synthesized these perspectives to identify the patterns of connection between the overlapping works of these professionals. A grounded theory model is provided as a result of data analysis to efficiently illustrate the connection of conceptual insights shared. These include expected outcomes, professional successes, youth agency, and contextual factors. These elements converge to demonstrate how professionals$1 (Binfluence on youth outcomes develops.s